2014
DOI: 10.1002/dc.23222
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of intraocular lesions using vitreous humor and intraocular perfusion fluid cytology: Experience with 83 Cases

Abstract: An early diagnosis and treatment of intraocular diseases is necessary to maintain an acceptable degree of quality of life. For an accurate diagnosis, it is necessary to understand the anatomy of the eye. Giemsa staining is recommended in addition to Papanicolaou staining for cytologic diagnostic evaluation of intraocular diseases. Furthermore, for the diagnosis of clonality in intraocular lymphomas, it is often necessary to use ancillary molecular biological procedures, using vitreous fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Asteroid bodies were found in 4 cases. This finding is specific to asteroid hyalosis, which is an infrequent degenerative disease of unknown etiology [13,16]. In our study, as in previous studies, neutrophils and/or eosinophils were observed in all mycotic, parasitic or bacterial infections [3,12,14].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Asteroid bodies were found in 4 cases. This finding is specific to asteroid hyalosis, which is an infrequent degenerative disease of unknown etiology [13,16]. In our study, as in previous studies, neutrophils and/or eosinophils were observed in all mycotic, parasitic or bacterial infections [3,12,14].…”
Section: Discussionsupporting
confidence: 74%
“…Of these cell types, epithelial cells were the most frequently observed. Some cells of the retina have been previously observed in vitreous fluid, such as Müller's cells, pigmented epithelial cells, rod cells and ganglion cells [13]. It has been reported that retinal cells can appear as round cells and be misinterpreted as malignant cells in some cases when stained by the PAP method [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations